Book Reviews (Historia, 2021)
1. Kees, Hermann: Ancient Egypt. A Cultural Topography  2. Harting, Pieter, 1812-1885: Mijne Herinneringen 3. Coolhaas, W. Ph.: A Critical Survey of Studies on Dutch Colonial History4. Botha, D. P.: Die Opkoms van ons Derde Stand 5. Roodt, A. G.: Afrika na 1939